1999
DOI: 10.1046/j.1365-2885.1999.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated administration of trimethoprim/sulfadiazine in the horse –pharmacokinetics, plasma protein binding and influence on the intestinal microflora

Abstract: Six healthy adult horses were given repeated administrations of trimethoprim/ sulfadiazine (TMP/SDZ) intravenously (i.v.) (2.5 mg/kg TMP and 12.5 mg/kg SDZ) and orally (p.o.) as a paste (5 mg/kg TMP and 25 mg/kg SDZ). Both formulations were given twice daily for 5 days, with a 3-week interval between i.v. and oral administration. The influence of the drug combination on the intestinal microflora was examined and the plasma concentrations, pharmacokinetic parameters and plasma protein binding were determined. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 17 publications
5
45
2
Order By: Relevance
“…However, in the latter study, a very high dose of SDZ (100 mg/kg bw) was used and this could have led to a capacity-limited elimination process (Van Gogh, 1980). Shorter terminal half-lives, relatively closer to the ¢ndings of the present study in sheep, have been reported in other animal species: *3.5^4.5 h in cattle (Clarke et al, 1989;Shoaf et al, 1989;Kaartinen et al, 1999), *4.6 h in horses (Van Duijkeren et al, 1994a, Gustafsson et al, 1999, and *3 h in chickens (Batzias et al, 2000;Baert et al, 2003). The bioavailability (+SD) of 69.00%+10.51% was found to be lower than that reported by Shoaf and colleagues (1987), who studied the bioavailability of SDZ after s.c. administration of a SZD/TMP combination in calves, as well as by Kaartinen and colleagues (1999), after either i.m.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, in the latter study, a very high dose of SDZ (100 mg/kg bw) was used and this could have led to a capacity-limited elimination process (Van Gogh, 1980). Shorter terminal half-lives, relatively closer to the ¢ndings of the present study in sheep, have been reported in other animal species: *3.5^4.5 h in cattle (Clarke et al, 1989;Shoaf et al, 1989;Kaartinen et al, 1999), *4.6 h in horses (Van Duijkeren et al, 1994a, Gustafsson et al, 1999, and *3 h in chickens (Batzias et al, 2000;Baert et al, 2003). The bioavailability (+SD) of 69.00%+10.51% was found to be lower than that reported by Shoaf and colleagues (1987), who studied the bioavailability of SDZ after s.c. administration of a SZD/TMP combination in calves, as well as by Kaartinen and colleagues (1999), after either i.m.…”
Section: Discussionsupporting
confidence: 88%
“…Studies in other species, such as swine (Nielsen and Rasmussen, 1975a,b;Garwacki et al, 1996), dogs and cats (Craig and White, 1976;Sigel et al, 1981), horses (Brown et al, 1983;Bogan et al, 1984;Van Duijkeren et al, 1994a, Gustafsson et al, 1999, poultry (Lo« scher et al, 1990;Batzias et al, 2000;Baert et al, 2003), rabbits (Ladefoged, 1977) and ¢sh (Nouws et al, 1993), have also been performed. All investigators clearly reported higher values of volume of distribution (V) and clearance (Cl), together with a substantially shorter elimination half-life for TMP, compared to SDZ.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using direct sequencing methods have revealed a greater diversity of horse microbiota than previously estimated by culture-dependent methods (Gustafsson et al, 1999). Previous were insufficient to fully understand the horse microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous were insufficient to fully understand the horse microbial communities. Direct sequencing analysis was used to study the gut microbiota of Irish Thoroughbred race horses in a recent study (O’Donnell et al, 2013), Ponies (Gustafsson et al, 1999) and so on. We examined and compared the composition and variation in the fecal microbiota of two horse breeds, Mongolian horses and Thoroughbred horses, using the high-throughput sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in equine practice that potentiated sulfonamides achieve the 1:20 plasma ratio and can be regarded to as therapeutically effective for susceptible S. equi when administered at 5 mg of TMP/kg of body weight and 25 mg of SDZ/kg (1:5 ratio) with a dosing interval of 12 h (1519). The results support the available literature, since the FIC indices showed synergy at a wide range of TMP-to-sulfonamide ratios and concentrations.…”
Section: Textmentioning
confidence: 99%